In utero exposure to poly- and perfluoroalkyl substances and children respiratory health in the three first years of life - Philippat, Claire; Coiffier, Ophélie; Lyon-Caen, Sarah; Boudier, Anne; Jovanovic, Nicolas; Quentin, Joane; Gioria, Yoann; Haug, Line Smastuen; Thomsen, Cathrine; Bayat, Sam; Slama, Rémy; Siroux, Valérie (Environmental research, 2023)
Poly- and perfluoroalkyl substances (PFAS) are used in a wide range of products. Experimental studies suggested impaired lung development and pro-inflammatory response following exposure to some PFAS. We aimed to assess the associations between prenatal exposure to PFAS and children respiratory health. The study is based on 433 mother-child pairs. 26 PFAS were measured in maternal serum collected during pregnancy. Lung function parameters were measured at 2 months using tidal breathing flow-volume loops and multiple-breath nitrogen washout and at 36 months using oscillometry. Incidence of respiratory health diseases (asthma, wheeze, bronchitis, bronchiolitis) in the first 36 months of life was assessed by repeated questionnaires. A cluster-based analysis was applied to identify prenatal PFAS exposure patterns. Adjusted linear and logistic regressions were performed to assess the associations between PFAS exposure patterns as well as individual PFAS, and each respiratory health parameter. We excluded 13 PFAS due to low quantification (<5%). Relying on the 13 remaining PFAS, we identified three exposure clusters, characterized by low (N = 163), medium (N = 236) and high (N = 51) pregnancy PFAS concentrations. Compared to children belonging to the low exposure group, children in the moderate exposure group had higher reactance at 7 Hz (X7) and lower frequency dependence of resistance between 7 Hz and 19 Hz (R7-19) at 36 months, suggesting better lung function. No association of any exposure metric was detected with respiratory diseases in the first 3 years of life. Our study relying on both mixture and uni-pollutant analyses, does not provide evidence for a deleterious effect of prenatal PFAS exposure on respiratory health at an early age. •We measured 13 per- and polyfluoroalkyl substances in maternal serum.•A cluster-based analysis was applied to identify prenatal PFAS exposure patterns.•The moderate exposure group tended to have improved lung function at 36 months.•No association was detected with respiratory diseases in the first 3 years of life.•Overall, our study does not show a deleterious respiratory health effect of PFAS.